Evaluasi Pelayanan Penanggulangan Bencana Kebakaran oleh Pemerintah Kecamatan - M. Harry Mulya Zein; Sisca Septiani (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2021)
This study evaluates the quality of local government public services in fire disaster management. Using a descriptive qualitative approach, this study focuses on interviews, observation, and documentation techniques for data analysis. The results identified a shortage of firefighting equipment and a significant reliance on the sub-district as the primary coordinator with the DPKPB. Despite rapid response efforts from the subdistrict government, more public education on fire prevention and handling still needs to be done. The main challenges are inhibiting factors such as natural conditions, lack of public awareness, and lack of infrastructure. This research suggests improved equipment provision, more effective community outreach, infrastructure development, and coordination between agencies and communities to quickly and efficiently respond to fire emergencies.